Homogeneous analysis of globular clusters from the APOGEE survey with the BACCHUS code – III. ω Cen. Issue 2 (28th April 2021) - Mészáros, Szabolcs; Masseron, Thomas; Fernández-Trincado, José G; García-Hernández, D A; Szigeti, László; Cunha, Katia; Shetrone, Matthew; Smith, Verne V; Beaton, Rachael L; Beers, Timothy C; Brownstein, Joel R; Geisler, Doug; et al.
ABSTRACT: We study the multiple populations of ω Cen by using the abundances of Fe, C, N, O, Mg, Al, Si, K, Ca, and Ce from the high-resolution, high signal-to-noise (S/N > 70) spectra of 982 red giant stars observed by the SDSS-IV/APOGEE-2 survey. We find that the shape of the Al–Mg and N–C anticorrelations changes as a function of metallicity, continuous for the metal-poor groups, but bimodal (or unimodal) at high metallicities. There are four Fe populations, similarly to previous literature findings, but we find seven populations based on Fe, Al, and Mg abundances. The evolution of Al in ω Cen is compared to its evolution in the Milky Way and in five representative globular clusters. We find that the distribution of Al in metal-rich stars of ω Cen closely follows what is observed in the Galaxy. Other α-elements and C, N, O, and Ce are also compared to the Milky Way, and significantly elevated abundances are observed over what is found in the thick disc for almost all elements. However, we also find some stars with high metallicity and low [Al/Fe], suggesting that ω Cen could be the remnant core of a dwarf galaxy, but the existence of these peculiar stars needs an independent confirmation. We also confirm the increase in the sum of CNO as a function of metallicity previously reported in the literature and find that the [C/N] ratio appears to show opposite correlations between Al-poor and Al-rich stars as a function of metallicity.